UJI TOKSISITAS AKUT EKSTRAK ETANOL KELOPAK ROSELLA (Hibiscus sabdariffa L.) PADA TIKUS Sprague Dawley - Fita Sari; Nurkhasanah Nurkhasanah; Moch. Saiful Bachri (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Roselle (Hibiscus sabdariffa L.) was used as a traditional medicine because it has antioxidant activity. Traditional medicine used to treat a disease should consider the safety aspects through the toxicity tests. This study aims to determine the acute toxicity of the ethanolic extract from the calyx of Hibiscus sabdariffa L., activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and hepar histopathology in Sprague Dawley (SD) rats. Acute toxicity tests was done by orall administration of single dose ethanolic extract at dose 40, 200, 1000 and 5000 mg/kg BB. The test was observed during 14 days post treatment. The activity of AST, ALT and ALP were measured by specthrophotometer UV-Vis Diasys® method. The results showed that LD50 of ethanolic extract of calyx roselle was found at 850,90 mg/kg BW, the activity of AST, ALT, ALP did not different significantly in the treatment to be and control group (p <0.05) and histopathological data found structural change and tissue in hepar. Tthe delayed toxic effects until day 14 was also not found. These research found that ethanolic extract of calyx roselle was toxic SDrats.